2019
DOI: 10.1002/ana.25607
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of KV2.1 Dysfunction in KCNB1‐Associated Neurodevelopmental Disorders

Abstract: Objective Pathogenic variants in KCNB1, encoding the voltage‐gated potassium channel KV2.1, are associated with developmental and epileptic encephalopathy (DEE). Previous functional studies on a limited number of KCNB1 variants indicated a range of molecular mechanisms by which variants affect channel function, including loss of voltage sensitivity, loss of ion selectivity, and reduced cell‐surface expression. Methods We evaluated a series of 17 KCNB1 variants associated with DEE or other neurodevelopmental di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 42 publications
5
74
0
1
Order By: Relevance
“…A recent paper on Kv2.1-related neurodevelopmental disorders documented a spectrum of Kv2.1 mutations (50). Among pathogenic mutations that did not affect current density, negative shifts in the voltage dependence of inactivation in the order of 10 to 20 mV were observed that would sufficiently reduce channel availability, resulting in a loss of function (50).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper on Kv2.1-related neurodevelopmental disorders documented a spectrum of Kv2.1 mutations (50). Among pathogenic mutations that did not affect current density, negative shifts in the voltage dependence of inactivation in the order of 10 to 20 mV were observed that would sufficiently reduce channel availability, resulting in a loss of function (50).…”
Section: Discussionmentioning
confidence: 99%
“…HEK293T cells were transfected with WT rat K v 2.1 in pRBG4, rat K v 2.1 S586A in pCGN, HA-tagged WT human K v 2.1, or HA-tagged WT human K v 2.1 with the G379R mutation ( Shi et al, 1994 ; Lim et al, 2000 ; Kang et al, 2019 ). Cells were transiently transfected using Lipofectamine 2000 following the manufacturer’s protocol within 18 h of plating.…”
Section: Methodsmentioning
confidence: 99%
“…In 30–50% of infants diagnosed with an epileptic encephalopathy, a causative mutation has been identified in a known epilepsy gene ( McTague et al, 2016 ). Previous work has identified heterozygous de novo KCNB1 pathogenic variants in individuals with DEE ( Torkamani et al, 2014 ; Saitsu et al, 2015 ; Thiffault et al, 2015 ; Allen et al, 2016 ; Calhoun et al, 2017 ; de Kovel et al, 2017 ; Latypova et al, 2017 ; Marini et al, 2017 ; Miao et al, 2017 ; Bar, 2020 ; Kang et al, 2019 ). In addition to seizures, individuals with KCNB1 variants display comorbidities that include developmental delay, intellectual disability, features of autism spectrum disorder, ADHD and aggression, as well as borderline long QT syndrome in some cases ( Calhoun et al, 2017 ; de Kovel et al, 2017 ; Marini et al, 2017 ; Bar, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of the affected protein is also important, and neuronal proteins that influence action potentials such as SCN9A have such critical roles that even minor alterations can be deleterious or fatal. 43 Some genetic risk modifiers may only become relevant in individuals also exposed to other environmental or genetic risks or in specific ethnicities or locations. 44 46 Recent mutations (sporadic cases with no family history) and those with incomplete penetrance are also underestimated.…”
Section: Discussionmentioning
confidence: 99%